REKONSTRUKSI SEJARAH DALAM KUMPULAN PUISI DARI BATAVIA SAMPAI JAKARTA MELALUI PEMBACAAN JAUH BERBASIS KORPUS - Bintang Purwaramdhona, Ananda; Hidayatullah, Mochamad Irfan; Rahayu, Lina Meilinawati (UI Scholars Hub, 2023)
By applying the mixed research methods combining new historicism and digital humanities with AntConc-assisted distant reading techniques, this research aims to explore a reconstruction of Jakarta's history offered in From Batavia to Jakarta (1619–1999), a collection of poems by Zeffry J. Alkatiri. Results show that history can be reconstructed through the physical structure of narrative poetry represented by the dominant usage of pronoun